SYNTHESIS AND INFRARED STUDY OF SOME PHENYLPHOSPHONATE, DIPHENYLPHOSPHINATE AND ACETATOPHOSPHONATE NEW ORGANOTIN (IV) DERIVATIVES AND ADDUCTS - MODOU SARR; AMINATA DIASSE-SARR; LIBASSE DIOP (Journal of Engineering Studies and Research)
Three organotin (IV) derivatives PhPO3HSnBu2Cl, SnBu2Ph2PO2Cl×3/2H2O, Sn(PhPO3)Cl2×2H2O obtained on allowing PhPO3H2 or propylammonium PhPO3H to react with SnBu2Cl2, SnCl2×2H2O and two adducts [(C6H5CH2)2NH2]3O2C(CH2)2PO3×3SnPh3Cl, [CyNH3(HO2POCH2-N(CH2CO2H)2]2×3SnCl4.2H2O×NH4Cl obtained on allowing (C6H5CH2)NH2)3O2C(CH2)2PO3 or [CyNH3(HO2POCH2-N(CH2 CO2H)2]2 and SnPh3Cl or SnCl2×2H2O to react in ethanolic media have been characterized by elemental analyses, infrared and Mossbauer techniques. The suggested structures, while considering the anionic counterpart, are discrete, dimeric, double and triple metallic components or of infinite chain types, the anion behaving as a monochelating, a bichelating or a bidentate ligand. In OH containing structures, when extra hydrogen bonds are considered, supramolecular architectures may be obtained.